CONSTRUCTION AND ANALYSIS OF A SALT GRADIENT SOLAR POND FOR HOT WATER SUPPLY - Aizaz, Ahmad; Yousaf, Rizwan (European Scientific Journal, ESJ, 2013)
Solar pond technology is being used in this world for the past many years, yet this technology has to prove its effectiveness in energy starved country like Pakistan and resolve energy crisis of the country. This research discusses basic principles of solar pond design, construction of a prototype solar pond, thermal energy extraction from the solar pond and cost benefit analysis of this technology for industrial sector in Pakistan in the form of a case study.